Genetic assessment of the dairy cattle Mambi de Cuba - Hern?ndez, Arelis; Ponce de Le?n, Raquel; Garc?a, Sonia M.; Guzm?n, Gladys; Mora, Marta (Cuban Journal of Agricultural Science, 2011)
Records, between 1980 and 2006, of dairy females of the Mambi de Cuba breed (3/4 Holstein 1/4 Zebu), from four cattle rearing units were used to estimate the parameters and genetic tendencies of the growth traits up to reproduction (17 434 heifers), milk yield (50 420 lactations of 20 687 cows), reproduction (16 526 reproductive events of 5 881 cows), longevity (11 338 cows), survival and permanence (12 865 cows). A univariate animal model was used for estimating heritability, repeatability and breeding values, including the year-four month period-herd combination and the calving year as linear and quadratic co-variable as fixed effects, and the permanent environment and error as random effects. The heritabilities had values from moderate to low, with higher estimates for the weight per incorporation age (WIA) (0.20), calving interval (CI) (0.06), milk yield up to 244 d (M244) and 305 d (M305) (0.15), fat percentage (FP) (0.19), calving number (CN) (0.06) and 18 months of productive life (S18) (0.05). The highest repeatability estimate was for M244 y M305, with 0.42. The genetic tendencies for WIA, CI, M305, productive life (PL) and P36 were of 0.02 ? 0.01 g/d/year, -1.53 ? 0.16 d/year, -2.52 ? 1.10 kg/year, 0.05 ? 0.03 months/year and 0.0004 ? 0.0002 months/year, respectively. It was concluded that there was no change in the population means because the genetic tendencies had low values (between 0.001 and 0.31 % of the mean), due to the instability of the progeny tests and to the little female selection. Key words: longevity, Mambi de Cuba, parameters, genetic tendencies, milk yield, reproduction.